Rheumatic Care in Under‐Resourced Areas Using the Extension for Community Healthcare Outcomes Model. Issue 6 (10th May 2020) - Bankhurst, Arthur; Romero‐Olivas, Cynthia; Hernandez Larson, Jessica; Bradford, Andrea; Fields, Roderick; Kalishman, Summers; Marquez, Marisa; Gonzales‐Van Horn, Sarah; Jones, Jessica; Burke, Tom; Snead, Jennifer; Arora, Sanjeev
Abstract : Objective: To demonstrate the effectiveness of the Extension for Community Healthcare Outcomes (Project ECHO) in educating primary care clinicians (PCCs) to provide best practice rheumatic care to patients in under‐resourced communities in New Mexico. Methods: Attendee data for weekly teleECHO sessions, lectures, grand rounds, and mini‐residency trainings were evaluated from June 2006 to June 2014. Participant feedback was evaluated from January 2009 to December 2014, when the program was approved for continuing medical education (CME) credits. Retrospective review of diagnoses associated with case presentations was conducted from June 2006 to June 2014 to evaluate the types of cases presented. A focus group was conducted with a convenience sample of 8 New Mexico PCCs who participated in ECHO Rheumatology (ECHO Rheum) for 1 year or longer. Results: Over the course of 9 years, ECHO Rheum educated 2, 230 clinicians, consisting primarily of physicians (53%) and nurse practitioners (22%). A total of 1, 958 CME credits were awarded to those who participated. There were 1, 173 cases presented; 85% of the cases reflected the 3 most common diagnoses: rheumatoid arthritis (n = 715), fibromyalgia (n = 241), and systemic lupus erythematosus (n = 54). In addition, ECHO Rheum conducted 15 two‐day mini‐residencies involving 30 PCCs; 21 of these clinicians subsequently completed the American College of Rheumatology online certification. Conclusion: Results from this study demonstrate that participation in ECHO Rheum provides clinicians in under‐resourced areas access to best‐practice knowledge and training in rheumatology.